Application of group V polyoxometalate as an efficient base catalyst: a case study of decaniobate clusters. Issue 20 (9th February 2016) - Hayashi, Shun; Yamazoe, Seiji; Koyasu, Kiichirou; Tsukuda, Tatsuya
Abstract : We demonstrated for the first time that [Nb10 O28 ] 6− exhibited base catalytic activity for aldol-type condensation reactions including Knoevenagel and Claisen–Schmidt condensation reactions. Abstract : The base catalytic activity of the decaniobate cluster (TMA)6 [Nb10 O28 ]·6H2 O (TMA + = tetramethylammonium cation) was studied theoretically and experimentally. Density functional theory calculations showed that the oxygen atoms in the cluster are highly negatively charged and suggested the possibility that the cluster can act as a base catalyst. We demonstrated for the first time that [Nb10 O28 ] 6− actually exhibits base catalytic activity for aldol-type condensation reactions including Knoevenagel and Claisen–Schmidt condensation reactions. The catalytic reactions proceeded under ambient conditions, suggesting that [Nb10 O28 ] 6− holds promise as a practical strong base catalyst.